Agreement between noninvasive oscillometric and invasive blood pressure measurements in isoflurane-anesthetized guinea pigs (Cavia porcellus). (March 2021) - Waxman, Samanta; Fuensalida, Santiago; Sánchez, Fernanda; Zárate, Indiana; Turnes, Emmanuel; Rodríguez, Casilda; Otero, Pablo
Abstract: Objective: To assess the agreement between an oscillometric device and invasive blood pressure (IBP) measurements in anesthetized healthy adult guinea pigs. Study design: Prospective experimental study. Animals: A total of eight adult Hartley guinea pigs. Methods: All animals were anesthetized; a carotid artery was surgically exposed and catheterized for IBP measurements. A size 1 cuff placed on the right thoracic limb was connected to an oscillometric device for noninvasive blood pressure (NIBP) assessment. Concurrent pairs of systolic (SAP), diastolic (DAP) and mean (MAP) arterial pressures were recorded simultaneously with both methods every 3 minutes for 30 minutes. Agreement between IBP and NIBP measurements was determined using the Bland–Altman method, considering the recommended standards for the validation of NIBP measurement devices proposed by the American College of Veterinary Internal Medicine (ACVIM). Results: The bias and the 95% limits of agreement were: –14 (–31 to 3) mmHg, –2 (–14 to 10) mmHg and –1 (–13 to 11) mmHg for SAP, DAP and MAP, respectively. Conclusions and clinical relevance: The oscillometric device used in this study to measure NIBP did not meet ACVIM criteria for validation. It showed good agreement for DAP and MAP but not for SAP measurements. Considering the small size of these animals and the resulting difficulty in performing percutaneous arterial catheterization, this device might be a useful tool to assess MAP and DAP during anesthetic procedures in adult guinea pigs.